Case Study of the Implementation of Foot Gymnastics for Diabetes Mellitus Patients in Pekuncen Village, Kebumen Regency: Studi Kasus Penerapan Senam Kaki pada Penderita Diabetes Mellitus di Desa Pekuncen Kabupaten Kebumen - Silviah, Anita; Yuda, Hendri Tamara (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Diabetes Mellitus is a disease characterized by unstable blood glucose levels. It is caused due to poor food control. Unless treated properly, it will cause stroke, heart attack, kidney failure, and severe leg infection (foot ulcers). To reduce blood glucose level, diabetic foot exercises is advisable as a non-pharmacological therapy.Providing an overview of nursing care for diabetes mellitus sufferers by applying diabetic foot exercise to lower blood glucose level. This scientific paper is an analytical descriptive with a case study approach. The respondents were 3 diabetes mellitus sufferers. Data was obtained through interviews, observations. After applying foot exercise, there was a decrease in glucose level of all respondents, as much as 19-45 mg / dl. Foot exercise can be applied as a non-pharmacological therapy to control blood glucose levels of diabetes mellitus sufferers.